2012
DOI: 10.1532/hsf98.20111062
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Appendage Aneurysm with Paroxysmal Atrial Fibrillation

Abstract: Aneurysm of the left atrial appendage is extremely rare, and afflicted patients most commonly present with atrial tachyarrhythmia or thromboembolism. For these patients, resection of the aneurysm is the recommended and preferred therapy. We present the case of a 57-year-old woman who was found incidentally to have a large aneurysm of the left atrial appendage presenting as atrial fibrillation. After surgical intervention with resection of the aneurysm and a Cox maze III procedure, the patient recovered and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…As the manipulation of aneurysm during surgery may dislodge thrombi, cardiopulmonary bypass is instituted if preoperative or intraoperative echocardiogram shows a thrombus or a large LAAA. [67][68][69][70] In centers that do not perform these procedures, excision of LAAA alone appears to be a reasonable choice. 52 Surgical or endoscopic resection eliminates the risk of both thromboembolism and tachyarrhythmia.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…As the manipulation of aneurysm during surgery may dislodge thrombi, cardiopulmonary bypass is instituted if preoperative or intraoperative echocardiogram shows a thrombus or a large LAAA. [67][68][69][70] In centers that do not perform these procedures, excision of LAAA alone appears to be a reasonable choice. 52 Surgical or endoscopic resection eliminates the risk of both thromboembolism and tachyarrhythmia.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Although endoscopic resection may be appropriate for smaller congenital aneurysms, the technique increases surgical difficulty and may be more popular in otherwise healthy young patients. The Cox–Maze III procedure is considered prudent in cases of atrial enlargement, basal aneurysmal dilatation, or persistent atrial fibrillation [13]. After surgery, there are almost no reports of recurrent symptoms, except in one patient who remained in atrial fibrillation after numerous attempts at defibrillation [4].…”
Section: Discussionmentioning
confidence: 99%
“…We performed contrast echocardiography to exclude the possible existence of thrombi. This method may be more suitable for a giant LAAA with an irregular form [13]. Also, progressively declining flow velocities through the orifice is a dangerous signal of blood stasis in LAAA [14].…”
Section: Discussionmentioning
confidence: 99%
“…Freedom from atrial fibrillation has been shown to range from six months to eight years following aneurysmectomy [2]. Certain centres employ the use of the Cox-Maze III procedure as an adjunct to reduce fibrillation recurrence [1,9]. Case studies employing these methods have shown no significant peri-or post-operative morbidity or mortality, and boast high rates of conversion to sinus rhythm, albeit at the cost of a small probability of atrioventricular block.…”
Section: Discussionmentioning
confidence: 99%
“…Case studies employing these methods have shown no significant peri-or post-operative morbidity or mortality, and boast high rates of conversion to sinus rhythm, albeit at the cost of a small probability of atrioventricular block. The Cox-Maze III procedure may be prudent in cases of biatrial enlargement, basal aneurysmal dilatation or persistent atrial fibrillation [9].…”
Section: Discussionmentioning
confidence: 99%